Experimental evaluation of natural hydraulic lime renders with nanoclay and nanolime to protect raw earth building surfaces. (December 2022) - Stazi, Francesca; Pierandrei, Nicola; Di Perna, Costanzo; Tittarelli, Francesca
Abstract: In this study Natural Hydraulic Lime (NHL) was combined with clay and lime, the main cementitious materials used in ancient buildings, to develop a new render more suitable for applications on raw earth substrates. Nanoclay and nanolime have been separately added to a commercial NHL-based ready-mixed powder. Pure and nano-additivated NHL renders have been compared in terms of microstructure (by SEM and mercury porosimetry), mechanical performance (by dynamic elastic modulus, flexural and compressive strength tests), adhesion to the substrate (by shear strength and pull-off tests), erosion resistance (by pressure spray test), and thermo-hygrometric performance (by water absorption and thermal conductivity tests). The obtained results demonstrate that both nanoparticles increase the water absorption and decrease the mechanical properties of the render but enhance the adhesion with the earthen support and the protection against water erosion. Among the two nanoparticles, the addition of nanoclay was found to be preferable since it gives to the render the highest mechanical compatibility with the underlying layer and the best durability against erosion.